VD_FINDINFO 170/2011/PHC vom 7. Dezember 2011 - VD Tribunal cantonal (2011)
APPEL EN CAUSE, COMPÉTENCE RATIONE LOCI, CONNEXITÉ MATÉRIELLE, LITISPENDANCE | 83 al. 1 let. b CPC, 86 al. 1 CPC, 36 LFors, 81 CPC (CH)